Configuration of a communicative citizenship in Medellín, Colombia, 1990-2010 - García-Bustamante, Elva-Mónica (2018)
This article reports partial results of the doctoral research oncommunication-related contributions conducted in Medellin, in the context of citizen education processes developed by third-sector organizations and territorial entities, in favor of the promotion of dialogue scenarios, participation and life alternatives for the inhabitants of the city. The communicationstrategies developed in this framework from the nineties demarcated notions and communication methodologies that were appropriated by the community for the intervention in its neighborhoods. From that point, platforms for interaction with other social actors were built by means of forming bonds thattoday could be understood as the exercise of a communicative citizenship.